Facile single-step synthesis of nitrogen-doped reduced graphene oxide-Mn3O4 hybrid functional material for the electrocatalytic reduction of oxygen - Bag, Sourav; Roy, Kanak; Gopinath, Chinnakonda S.; Raj, C. Retna (ACS Applied Materials & Interfaces, 2014)
Development of efficient electrocatalyst based on non-precious metal that favors the four-electron pathway for the reduction of oxygen in alkaline fuel cell is a challenging task. Herein, we demonstrate a new facile route for the synthesis of hybrid functional electrocatalyst based on nitrogen-doped reduced graphene oxide (N-rGO) and Mn3O4 with pronounced electrocatalytic activity towards oxygen reduction reaction (ORR) in alkaline solution. The synthesis involves one-step in situ reduction of both graphene oxide (GO) and Mn(VII), growth of Mn3O4 nanocrystals and nitrogen doping onto the carbon framework using a single reducing agent, hydrazine. The X-ray photoelectron (XPS), Raman and FTIR spectral, and X-ray diffraction measurements confirm the reduction of GO and growth of nanosized Mn3O4. The XPS profile reveals that N-rGO has pyridinic (40%), pyrrolic (53%), and pyridine N oxide (7%) types of nitrogen. The Mn3O4 nanoparticles are single crystalline and randomly distributed over the wrinkled N-rGO sheets. The hybrid material has excellent ORR activity and it favors the 4-electron pathway for the reduction of oxygen. The electrocatalytic performance of the hybrid catalyst is superior to the N-rGO, free Mn3O4 and their physical mixture. The hybrid material shows an onset potential of -0.075 V, which is 60-225 mV less negative than that of the other catalyst tested. It has excellent methanol tolerance and high durability. The catalytic current density achieved with the hybrid material at 0.1 mg cm(-2) is almost equivalent to that of the commercial Pt/C (10%). The synergistic effect of N-rGO and Mn3O4 enhances the overall performance of the hybrid catalyst. The nitrogen in N-rGO is considered to be at the interface to bridge the rGO framework and Mn3O4 nanoparticles and facilitates the electron transfer.
Keywords: electrocatalysis; hybrid material; Mn3O4; nitrogen-doped graphene; oxygen reduction; synergistic effect